Pajak Hiburan, Pajak Parkir dan Pajak Reklame terhadap Pendapatan Asli Daerah di Badan Pendapatan Daerah, Kabupaten Brebes - Dhina Nur Farida; Mukson; Yenny Ernitawati; Indah Dewi Mulyani; Amelia Sholeha (Universitas Muhadi Setiabudi, 2021)
Local Revenue (PAD) is an important part of the area which is considered as the level of government independence in the financial sector, especially the Brebes Regency Government. To increase PAD, local governments must be able to explore sources that can generate income in their areas that have the potential to be taxed. Entertainment tax, parking tax and billboard tax are local taxes. These three taxes can be a potential source of funding to provide income for the regional treasury to meet regional needs that can spur economic development in Brebes Regency. This study aims to determine the effect of entertainment tax, parking tax and billboard tax on Brebes Regency PAD in 2015–2019. This research is a quantitative descriptive study. The data used is secondary data. Data collection techniques are carried out through observation, interviews and literature studies. Data analysis using SPSS is descriptive statistical analysis, classical assumption test, multiple linear analysis test, t test, F test, and determination coefficient test. The results showed that the entertainment tax partially had a significant effect on PAD; parking taxes partially have a significant effect on PAD; the billboard tax partially affects pad significantly. Simultaneously, entertainment tax, parking tax and billboard tax have a significant effect on PAD.